If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -4(x + 9) = 0 Reorder the terms: X + -4(9 + x) = 0 X + (9 * -4 + x * -4) = 0 X + (-36 + -4x) = 0 Reorder the terms: -36 + X + -4x = 0 Solving -36 + X + -4x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '36' to each side of the equation. -36 + X + 36 + -4x = 0 + 36 Reorder the terms: -36 + 36 + X + -4x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + X + -4x = 0 + 36 X + -4x = 0 + 36 Combine like terms: 0 + 36 = 36 X + -4x = 36 Add '4x' to each side of the equation. X + -4x + 4x = 36 + 4x Combine like terms: -4x + 4x = 0 X + 0 = 36 + 4x X = 36 + 4x Simplifying X = 36 + 4x
| 5a+6=2a+12 | | 8(3n+7)=152 | | -5(x+1)-x-14=-6(x+4)+5 | | 8b+22=3b+32 | | 0=x^2-1x-12 | | 12+5k=-4k | | 6w-14w=40 | | 2t+16=6t-12 | | 6x^2-4x-32= | | 45-4=11 | | 3(22+54)= | | 3-2x-1=2x+5 | | X=(-1)-2y | | r-4=15 | | -3x+9+4x=10-24 | | 3(x+3)/2-2(2-3x)=8x-1-2(x+3) | | 8x-3=2x-7x+4 | | X+2x+(5+2x)=100 | | B=an+qforn | | (6*3)x+4+2x= | | -4+2x=-1 | | d(g)=40g | | 20-6x=150-4x | | 2(x+1)=3(3-2x)+1 | | -6x=-18x+3x | | -5y=-4x+27 | | -10+x=x+29 | | -3x+2y=-22 | | 4(x-2y)=56 | | -8+2y=-1 | | 3(a-6)=24 | | 3x^2+3y^2+12x-18y+27=0 |